Student engagement as the factor of math mastery in university: the relationship between social factor and learning practices - Abu Bakar, Nora’asikin; Mohd Ayub, Ahmad Fauzi; Ahmad, Nor Aniza; Syed Abdullah, Sharifah Intan Sharina (Science Research Society, 2021)
The main aim of math teaching at the higher level is to form students’ competency to prepare them for other courses that require mathematical skills and professional task solving. The challenge today is to develop student engagement in math learning. Thus, this study examined the relationship between social factors, student learning practices, and student engagement in math learning. A survey through questionnaires was distributed to 284 bachelor's degree students at a private university in Malaysia. For data analysis, descriptive statistics and Structured Equation Modeling were applied. The results obtained revealed that there were significant relationships between: a) teaching practices and attentive listening, note-taking, working on in-class problems, b) peer influence and attentive listening, c) parental involvement and working on in-class problems, and the amountof homework completed. The results also show that seating location, attentive listening, note-taking, working on in-class problems, and homework completion have a significant relationship with student engagement in math learning.